2013
DOI: 10.6018/analesps.29.3.145171
|View full text |Cite
|
Sign up to set email alerts
|

La generatividad en la vejez y su relación con el bienestar: ¿Quién más contribuye es quien más se beneficia?

Abstract: Resumen: El objetivo de la investigación fue la adaptación al español de las escalas de interés y comportamientos generativos de McAdams, así como el estudio de la generatividad en la vejez y su relación con el bienestar. La muestra estuvo compuesta por 165 voluntarios mayores de 65 años que, además de las versiones españolas de las escalas de generatividad, completaron instrumentos para evaluar satisfacción con la vida y orientación al futuro. Los resultados indicaron que la fiabilidad de las versiones españo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
39

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 35 publications
2
31
0
39
Order By: Relevance
“…Einolf 2014; Gruenewald et al 2012). Previous studies have shown that generative concern is positively associated with a range of generative behaviours (Penezić et al 2008;Villar et al 2013). Higher levels of generative concern have also been positively associated with volunteering (Son and Wilson 2011) and some measures of social responsibility to family and community (Rossi 2001).…”
Section: Generativity: a Multidimensional Conceptmentioning
confidence: 86%
See 2 more Smart Citations
“…Einolf 2014; Gruenewald et al 2012). Previous studies have shown that generative concern is positively associated with a range of generative behaviours (Penezić et al 2008;Villar et al 2013). Higher levels of generative concern have also been positively associated with volunteering (Son and Wilson 2011) and some measures of social responsibility to family and community (Rossi 2001).…”
Section: Generativity: a Multidimensional Conceptmentioning
confidence: 86%
“…Hart et al 2001;Peterson and Duncan 1999), research on older people has been virtually non-existent. Some authors have highlighted the link between the wider concept of "civic engagement" and generativity in old age (Kleiber and Nimrod 2008;Villar and Serrat 2014a;Warburton et al 2006), but elders' political participation has not been systematically explored through the lens of generativity. To this end, the present study aims to explore older people's political participation, specifically participation through organisations, in relation to dimensions of generativity.…”
Section: Generativity In Old Agementioning
confidence: 98%
See 1 more Smart Citation
“…La versión española de esta escala (Villar et al, 2013) fue validada con una muestra de 165 AM de entre 65 y 100 años. El análisis factorial obtuvo dos factores que explican el 29% de la varianza (18,8% el factor Generatividad Positiva y 10,2% el factor Generatividad Dudosa).…”
Section: Instrumentos Que Evalúan La Generatividadunclassified
“…From the age of thirty, generativity takes place, given that this is the life stage in which it is common to create a family and/or engage in a job (Erikson, 2007). Generativity also supposes a challenge that the individual has to experience in order to face middle adulthood (Villar, López, & Celdrán, 2013). There are several characteristics of generativity: engagement in professional activities; involvement in social, religious or political organizations; and other actions that involve taking care of other people (Zacarés & Serra, 2011).…”
Section: Introductionmentioning
confidence: 99%